Remarks on some species of tardigrades from South America with the description of Minibiotus sidereus n. sp. - Pilato, Giovanni; Binda, Maria Grazia; Lisi, Oscar (Zootaxa, 2003)
Seven species of tardigrades are reported from Ecuador, one of which, Fractonotus caelatus (Marcus 1928) is new for South America and one, Minibiotus sidereus, is new for science. Minibiotus sidereus has circular, elliptical and star-shaped cuticular pearls (with 3-8 arms), pharyngeal bulb with large apophyses, three short macroplacoids and small microplacoid; the eggs have many conical processes with 6-7 annulations.